1994
DOI: 10.1007/bf01919382
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of fructose 2,6-bisphosphate in substrate cycle control in the nonoxidative stage of the pentose phosphate pathway. A phosphorus magnetic resonance spectroscopy study

Abstract: The role of fructose 2,6-bisphosphate in the interconversion of sedoheptulose 7-phosphate and sedoheptulose 1,7-bisphosphate in rat liver cytosol fractions was studied by means of phosphorus magnetic resonance spectroscopy. When the activity of 6-phosphofructo-1-kinase was inhibited by a high concentration of ATP, the addition of fructose 2,6-bisphosphate led to a marked decrease in sedoheptulose 7-phosphate levels, accompanied by an increased concentration of ADP. Fructose 2,6-bisphosphate essentially inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…These bisphosphates can be reconverted into their respective monophosphates by phosphofructose bisphophatases. A similar regulation pattern was reported for S7P and S1,7BP (see the text) [34][35][36][37][38][39][40][41]. Aldolase uses F1,6BP and S1,7BP as substrates to form DHAP and G3P or DHAP and E4P respectively.…”
Section: Metabolism Of Carbohydrate Phosphatessupporting
confidence: 66%
See 3 more Smart Citations
“…These bisphosphates can be reconverted into their respective monophosphates by phosphofructose bisphophatases. A similar regulation pattern was reported for S7P and S1,7BP (see the text) [34][35][36][37][38][39][40][41]. Aldolase uses F1,6BP and S1,7BP as substrates to form DHAP and G3P or DHAP and E4P respectively.…”
Section: Metabolism Of Carbohydrate Phosphatessupporting
confidence: 66%
“…Together, these results provide preliminary evidence for the coexistence of the hexose-and heptose-(bis)phosphate shunts ( Figure 3B). Notably, high glucose levels or incubation with F2,6BP augmented S1,7BP formation in perfused rat liver and in rat liver cytosol respectively [36,37]. Glucagon, in contrast with high glucose, favoured S1,7BP dephosphorylation and therefore S7P formation [36].…”
Section: Metabolism Of Carbohydrate Phosphatesmentioning
confidence: 96%
See 2 more Smart Citations
“…Inhibition of inducible PFK‐2 protein expression decreased the intracellular levels of PRPP, a product of the PPP and a precursor for nucleic acid biosynthesis. This observation suggested that the Fru‐2,6‐P 2 regulation of flux through PFK‐1 may affect the non‐oxidative PPP [11,12], which is the main source of ribose 5‐P in proliferating cells [13–15]. Moreover, the pentoses cycle contributes to the control of glucose metabolism and provides cells with NADPH for proliferation [16].…”
Section: Introductionmentioning
confidence: 99%